Investigation of Multi-layered Fire Doors with Gypsum Layer Exposed to Fire - Guobys, Remigijus; Mokshin, Vadim (Periodica Polytechnica Civil Engineering, 2021)
This article analyzes gypsum board dehydration effect on heat conductivity and deformation of multi-layered mechanical structures subjected to temperature changes. Specially designed structures (fire doors) consisting of steel sheets with stone wool and gypsum insulating layers in between were heated in furnace for a specified period of time of not less than 60 min. Temperature versus time curves and deformations of multi-layered structures were obtained. Experimental results were verified by numerical simulation. Experimental data was found to be in good agreement with numerical simulation results. The percent differences between door temperatures from simulation and fire test don’t exceed 9 %. This shows that thermal behavior of such multi-layered structures can be investigated numerically avoiding time-consuming and expensive fire tests. The data obtained allowed to calculate convective heat transfer coefficient of gypsum board, which was fitted into multi-layered mechanical structure. It was found that it is more advantageous to place gypsum layer in the middle of the structure rather than closer to the fire source in order to cool the structure more efficiently during fire.